Global View of Ionospheric Disturbance Impacts on Kinematic GPS Positioning Solutions During the 2015 St. Patrick's Day Storm. Issue 7 (20th July 2020) - Yang, Zhe; Morton, Y. T. Jade; Zakharenkova, Irina; Cherniak, Iurii; Song, Shuli; Li, Wei
Abstract: The 2015 St. Patrick's Day geomagnetic storm caused numerous disturbances of the ionosphere, particularly, plasma irregularities, large‐scale traveling ionospheric disturbances, and equatorial ionization anomaly enhancement. This study for the first time quantifies the global‐scale impacts of the ionospheric disturbances on Global Positioning System (GPS) precise point positioning (PPP) solutions during this extreme space weather event by taking advantage of 5, 500 + GNSS stations installed worldwide. The overall impact was more severe at high latitudes, while PPP degradation at low latitudes was associated with different types of ionospheric disturbances. Specifically, our results show that kinematic PPP solutions degraded following an intensified auroral particle precipitation during the storm's main phase (06–23 UT) when up to ~70% of the high‐latitude stations experienced degraded position solutions in the multimeter range at 16–18 UT. Around magnetic noon and midnight, the storm‐induced plasma irregularities caused notable PPP errors (>10 m) at high latitudes. Interhemispheric differences were observed with a more severe impact seen in the Southern Hemisphere, where PPP outage lasted for ~12 hr during the second main phase (12–23 UT). At low latitudes, post sunset equatorial plasma irregularities were suppressed across most longitudes, but large PPP errors (>2 m) associated with storm‐induced plasma bubbles were registered at the Indian sector at 14–18 UT. The storm‐induced equatorial ionization anomaly enhancement and large‐scale traveling ionospheric disturbances were responsible for the low‐latitude PPP degradation at dayside sectors. This study fills the research gap between physical and practical aspects of severe ionospheric storm effects. Key Points: Ionospheric disturbances caused high‐precision GPS positioning degradation on a global scale during the 2015 St. Patrick's Day storm At high latitudes, severe position degradation was observed around magnetic noon and midnight coinciding with plasma irregularities zone At low latitudes, position errors were due to storm‐induced plasma bubbles, EIA enhancement, and traveling ionospheric disturbances